Моделирование переходных режимов ядерного реактора ВВЭР-1000 с учетом борного регулирования - Никулина, Елена Николаевна; Северин, Валерий Петрович; Лукинова, Дарина Андреевна (НТУ "ХПИ", 2017)
Разработаны модели реактора ВВЭР-1000 в виде систем дифференциальных уравнений с относительными переменными состояния, описывающие нейтронную кинетику реактора, тепловые процессы, изменения концентраций ксенона и бора. Вычислены постоянные параметры математических моделей с учетом борного регулирования. На основании математических моделей реактора получены переходные процессы для ввода борной кислоты в реактор, проанализированы изменения важнейших переменных состояния активной зоны реактора.

The mathematical models of the VVER-1000 reactor of the V-320 series are constructed in the form of systems of differential equations with relative state variables describing the neutron kinetics of the reactor, gradual heat release, thermal processes, and changes in the concentrations of xenon and boron. The design parameters and parameters of the VVER-1000 reactor of the V-320 series are used to calculate the constant parameters of mathematical models, taking into account boron regulation. Based on mathematical models of the reactor, by numerical integration of differential equations, transient processes for introducing boric acid into the reactor have been obtained, which allows one to analyze changes in the most important variables of the state of the reactor core.
Modeling of transients of the WWER-1000 nuclear reactor taking into account boron regulation
Keywords: математическая модель; параметры модели; атомная электрическая станция; АЭС; система дифференциальных уравнений; СДУ; ДУ; mathematical model; model parameters